Acute Liver Failure During Deferasirox Chelation: A Toxicity Worth Considering. Issue 3 (April 2017) - Menaker, Nathan; Halligan, Katharine; Shur, Natasha; Paige, John; Hickling, Matthew; Nepo, Anne; Weintraub, Lauren
Abstract : This case report details a unique case of acute, reversible liver failure in a 12-year-old male with sickle cell anemia on chronic transfusion protocol and deferasirox chelation. There is substantial literature documenting deferasirox-induced renal injury, including Fanconi syndrome, but less documentation of hepatic toxicity and few reports of hepatic failure. The case highlights the importance of close monitoring of ferritin, bilirubin, and transaminases for patients on deferasirox.